Vocational Education and Training in Bulgaria Governance and Funding - Bergseng, Benedicte (OECD Reviews of Vocational Education and Training, 2019)
Over recent years, Bulgaria has shown great willingness to reform its vocational education and training (VET). Significant challenges remain, however, relating notably to the system’s responsiveness to labour market needs and its capacity to ensure equitable outcomes for learners. This report is a focused review of two predefined issues, the governance and funding of VET. These are two fundamental elements within the delivery of skilled VET graduates. The report assesses the strengths of the Bulgarian VET system and the challenges it faces when it comes to governance and funding and suggests policy responses for how these challenges can be addressed. Four specific challenges are identified linked to the governance of the VET system: decision-making powers and capacity; the use of data and evidence to inform policy decisions; social partner engagement; and, oversight of adult VET learning provision. With regard to VET funding, both school level financial autonomy, and the capacity to act upon increased flexibilities, are currently modest. The report argues that potential exists to strengthen collaboration between schools and employers to achieve increased cost-sharing between government and private firms. Finally, more can be done to improve equity in VET delivery through Bulgaria’s funding formula